Living in the shadow of a hell ship the survival story of U.S. Marine George Burlage, a WWII prisoner-of-war of the Japanese - Burlage, George 1918-2008 (North Texas military biography and memoir series, 2020)
"Book is a daughter's story of her father's experience as a Japanese POW in World War II. She has written an intro and assembled his notes and memoir of his experiences"--